1998
DOI: 10.1159/000028203
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of TRK-530 on Inflammatory Cytokines in Bone Marrow of Rats with Adjuvant Arthritis

Abstract: TRK-530 is a novel synthetic bisphosphonate compound which exhibits inhibitory activity in the rat adjuvant arthritis (AA) model. We found that, during AA development, the concentrations of cytokine-induced neutrophil chemoattractant-1 (CINC-1) and tumor necrosis factor α (TNF-α) in the bone marrow increased, and that administration of TRK-530 decreased the concentrations of these cytokines. The suppression of these concentration increases paralleled the inhibition of paw edema. Paw edema inhibition by TRK-530… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Previous studies have shown that TRK-530 can prevent rat adjuvant arthritis that might be the result of a decrease in inflammatory cytokines such as TNF-α and neutrophil chemoattractant (CINC)-1. A decrease in serum sialic acid, a systemic parameter of inflammation, has also been reported in TRK-530-treated animals with adjuvant arthritis (7,8). Based on these findings, we have been studying the effect of this compound on PGE 2 synthesis in organ culture of neonatal mouse calvaria.…”
Section: Inhibitory Effect On the Synthesis Of Pgementioning
confidence: 70%
“…Previous studies have shown that TRK-530 can prevent rat adjuvant arthritis that might be the result of a decrease in inflammatory cytokines such as TNF-α and neutrophil chemoattractant (CINC)-1. A decrease in serum sialic acid, a systemic parameter of inflammation, has also been reported in TRK-530-treated animals with adjuvant arthritis (7,8). Based on these findings, we have been studying the effect of this compound on PGE 2 synthesis in organ culture of neonatal mouse calvaria.…”
Section: Inhibitory Effect On the Synthesis Of Pgementioning
confidence: 70%
“…Here we observed an increase in serum sialic acid, a marker of rheumatoid arthritis (29), in GAS-infected mice. Experimental rats with adjuvant arthritis showed a similar increase in serum sialic acid (32). Therefore, some common mechanisms may underlie both septic arthritis and rheumatoid arthritis.…”
Section: Vol 71 2003 Gas Induces Septic Arthritis With Increased Ramentioning
confidence: 85%
“…Certain bacterial virulence factors such as superantigens and exotoxins have been implicated in S. aureus arthritis (33), and host immune responses were reported to be important in the induction and progression of this disease (12,32,35). Inflammatory cytokines such as interleukin-1 (IL-1), IL-6, and tumor necrosis factor alpha (TNF-␣) participate in the pathogenesis of septic arthritis (4).…”
mentioning
confidence: 99%
“…These are the subcutaneous injection of turpentine (Liao et al 1986;Bu¨rger et al 1987;Myers and Fleck 1988;Jinbo et al 2002) and the injection of FCA into the footpad (Sternberg et al 1974;Bu¨rger et al 1987;Connolly et al 1988;Tanahashi et al 1998). However, a third, less frequently used model involving the intraperitoneal (i.p.)…”
Section: Introductionmentioning
confidence: 99%